URGENSI PENERAPAN SISTEM CYBER NOTARY DITENGAH PANDEMI COVID 19 - Tamara Dwi Rizki Amanda; Wardani Rizkianti (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
Indonesia has designated the Covid-19 pandemic as a disease that causes a public health emergency and the government has issued several regulations requiring people to work from home. This research covers two main problems  First, how is the validity of notary deeds made by the cyber notary system? Second, what is the urgency of implementing a cyber notary system amid the Covid-19 pandemic? This writing uses normative juridical research. Notary deeds made by cyber notary have the power of proof as underhand deeds. The importance of implementing cyber notary amid a pandemic is strengthened one of which is the Minister of Health Regulation Number 9 of 2020 and Government Regulation Number 21 of 2020 which requires closing the office sector and working from home to break the line of the spread of the coronavirus in Indonesia.